Synthesis and characterisation of halogenated bis(acylthiourea) derivatives and its antibacterial activities - Ainaa Nadiah, Abd Halim; Zainab, Ngaini (Taylor & Francis, 2017)
A total of 12 bis(acylthiourea) derivatives with different pharmacophores have been synthesized via nucleophilic substitution reaction of benzene-1,4-dicarbonyl isothiocyanate intermediate with aromatic amine bearing halogens at the ortho, meta and para positions. The structures of the synthesised compounds were confirmed by CHN elemental analysis, FT-IR, ¹H NMR and ¹³C NMR spectroscopies. Antibacterial studies of the compounds via the Kirby Bauer disc diffusion method against Escherichia coli (E.coli) ATCC 25922 and Staphylococcus aureus (S. aureus) S48/81 demonstrated that bis(acylthiourea) N¹,N⁴-bis[(2-chlorophenyl)carbamothioyl]terephthalamide (4) and N¹,N⁴-bis[(2-bromophenyl)carbamothioyl]terephthalamide (7) bearing Cl and Br at the ortho position exhibited excellent activities against both bacteria strains compared to ampicillin standard.